Effectiveness evaluation of glyphosate oxidation employing the H2O2/UVC process: Toxicity assays with Vibrio fischeri and Rhinella arenarum tadpoles - Junges, Celina Maria (2013)
The H2O2/UVC process was applied to the photodegradation of a commercial formulation of glyphosate in water. Two organisms (Vibrio fischeri bacteria and Rhinella arenarum tadpoles) were used to investigate the toxicity of glyphosate in samples M1, M2, and M3 following different photodegradation reaction times (120, 240 and 360 min, respectively) that had differing amounts of residual H2O2. Subsamples of M1, M2, and M3 were then used to create samples M1,E, M2,E and M3,E in which the H2O2 had been removed. Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activities were measured in tadpoles to determine possible sub-lethal effects. In V. fischeri, M1,E, which was collected early in the photodegradation process, caused 52% inhibition, while M3,E, which was collected at the end of the photodegradation process, caused only 17% inhibition. Survival of tadpoles was 100% in samples M2, M3, and in M1,E, M2,E and M3,E. The lowest percentages of enzymatic inhibition were observed in samples without removal of H2O2: 13.96% (AChE) and 16% (BChE) for M2, and 24.12% (AChE) and 13.83% (BChE) for M3. These results show the efficiency of the H2O2/UVC process in reducing the toxicity of water or wastewater polluted by commercial formulations of glyphosate. According to the ecotoxicity assays, the conditions corresponding to M2 (11 ± 1 mg a.e. L−1 glyphosate and 11 ± 1 mg L−1 H2O2) could be used as a final point for glyphosate treatment with the H2O2/UV process.